Medicolegal Evaluation of Burn Injuries- An Autopsy Based Study - Pradeep Kumar Nayak1 , Bibhuti Bhusana Panda2 , Sudhansu Sekhar Sethi3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Even before the primitive man learnt to use fire, he has been a victim of it. Our study was carried out overa period of 2 years starting from 1st September 2012 to 31st August 2014 at SCB Medical College, Cuttack,Odisha on burn deaths. Aim and objective of the study was to know demographic pattern, cause of death andrelation of body surface involved.The rate of burn death was 16.7% of the total autopsy. Female victims outnumbered male victims with afemale to male ratio approximately 3.2 : 1. Majority of the cases belong to adolescent and young adult (11-40 years) age group. Maximum no. of victims were married. In most of the cases fatal period was within24 hours. Most of the deaths occurred when >40% of TBSA is involved. Most of the victims died within1 week. More than 80% of TBSA are involved in majority of cases of shock, whereas a wide range ofTBSA(30-100%) is involved in cases of septicaemia. Major cause of death in burn was septicaemia.